The Infrared Electrochromic Properties Based on Acid Doped-Polyaniline Films - Li, Bingzhen; Chen, Yuhua; Liu, Xinwei; Li, Fangyuan; Wang, Jijun; Li, Yan; Li, Ning (Frontiers in Materials, 2022)
In recent years, the infrared electrochromic devices based on acid doped polyaniline films have achieved much progress, which has not been summarized. This is important to accelerate the development of this field. In this paper, we will briefly review some representing work about the infrared electrochromic properties of acid doped polyaniline films, which were reported in the last five years.